Intracerebroventricular drug administration - Atkinson, Arthur J. (Transl Clin Pharmacol, 2017)
Among the various routes of drug administration, perhaps the least studied is intracerebroventricular (ICV) administration. This route has been shown to be particularly useful in administering to the central nervous system (CNS) drugs that do not cross the blood-brain barrier readily. As such, the ICV route is a valuable option for providing therapeutic CNS drug concentrations to treat patients with CNS infectious and neoplastic diseases. This route of drug administration also has the advantage of minimizing systemic toxicity.